Improving cooking quality of grain legumes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
A project to improve the cooking quality of grain legumes and their products has been undertaken in Kenya and Cameroon and coordinated by the Institute of Food Research based in Norwich, UK.Beans are inexpensive, rich sources of dietary proteins and...